Relationship between myelin sheath and neurological diseases: Specifically multiple sclerosis - narrative review (Research, Society and Development, 2025)
Multiple Sclerosis (MS) is an autoimmune and neurodegenerative disease of the Central Nervous System, characterized by demyelination mediated by autoreactive T lymphocytes, resulting in progressive neurological deficits. This study aimed to review the immunological and neurodegenerative mechanisms of MS, as well as emerging therapeutic strategies. A systematic review was conducted in the PubMed, SciELO, Web of Science, and LILACS databases, including articles published between 2010 and 2025, using descriptors such as "Multiple Sclerosis," "Demyelination," and "Autoimmunity." The results highlighted the role of pro-inflammatory cytokines, the influence of genetic (HLA-DRB1*15:01) and environmental (EBV, vitamin D) factors, and the importance of biomarkers such as neurofilament light chain (NFL) for diagnosis and prognosis. Therapies with monoclonal antibodies (such as ocrelizumab) and regenerative approaches (stem cells, microbiota modulation) have shown efficacy in controlling the disease. It is concluded that, although therapeutic advances have improved the management of MS, effective remyelination remains a challenge, requiring future research in neuroprotection and myelin repair.